An International Menopause Society study of vasomotor symptoms in Bangkok and Chiang Mai, Thailand. (4th March 2017) - Sriprasert, I.; Pantasri, T.; Piyamongkol, W.; Suwan, A.; Chaikittisilpa, S.; Sturdee, D.; Gupta, P.; Hunter, M. S.
Abstract: Objectives: To examine relationships between location, demographics, lifestyle, beliefs, and experience of hot flushes and night sweats (HFNS) amongst women living in two cities in Thailand. Methods: Cross-sectional study of peri- and postmenopausal women, aged 45–55 years, from Bangkok and Chiang Mai. Participants completed questionnaires (demographics, health, HFNS (prevalence, frequency and problem-rating) and beliefs about menopause). A sub-sample of women from each location was interviewed. Results: A total of 632 women (320 Bangkok and 312 Chiang Mai) aged 50.88 (standard deviation 3.06) years, took part. The prevalence of HFNS was 65%, average HFNS frequency 8.7 (10.8) per week and problem rating 4.3/10. Women from Chiang Mai had significantly more problematic HFNS, but prevalence and frequency were similar in both sites. Poor general health predicted HFNS prevalence and frequency, while Chiang Mai location, HFNS frequency, age, diet and beliefs about menopause were associated with problematic HFNS. Location remained significant after controlling for education, occupation and age; location was partially explained by beliefs. Qualitative interview responses illustrated the differences in beliefs about menopause between locations. Conclusion: HFNS reports are prevalent with moderate frequency and problem-ratings in these urban centers in Thailand. The results will be included in the broader International Menopause Society study of Climate, Altitude and Temperature (IMS-CAT) of the impact of climate on HFNS.